Transcriptional Regulation of Telomeric Expression Sites and Antigenic Variation in Trypanosomes - Cestari, Igor; Stuart, Ken (Current Genomics, 2018)
Introduction: Trypanosoma brucei uses antigenic variation to evade the host antibody clearance by periodically changing its Variant Surface Glycoprotein (VSGs) coat. T. brucei encode over 2,500 VSG genes and pseudogenes, however they transcribe only one VSG gene at time from one of the 20 telomeric Expression Sites (ESs). VSGs are transcribed in a monoallelic fashion by RNA polymerase I from an extranucleolar site named ES body. VSG antigenic switching occurs by transcriptional switching between telomeric ESs or by recombination of the VSG gene expressed. VSG expression is developmentally regulated and its transcription is controlled by epigenetic mechanisms and influenced by a telomere position effect. Conclusion: Here, we discuss 1) the molecular basis underlying transcription of telomeric ESs and VSG antigenic switching; 2) the current knowledge of VSG monoallelic expression; 3) the role of inositol phosphate pathway in the regulation of VSG expression and switching; and 4) the developmental regulation of Pol I transcription of procyclin and VSG genes.
Keywords: Epigenetic